Breastfeeding Practices of Karo Mothers in North Sumatera Indonesia - Milda Longgeita Pinem (HUMANISMA : Journal of Gender Studies, 2022)
This research aimed to understand the breastfeeding practices of mothers in Karo lands, North Sumatera, Indonesia. This research used ethnographic approach with data collection methods including participant observation, formal interviews and informal interviews. This research involved 27 participants. The research presented how Karo women's experiences of breastfeeding are influenced by three main institutional structures: the state, religion, and ethnic tradition. This study identified three essential points related to breastfeeding practices in Karo lands:  First, Karo mothers in the breastfeeding practice become an agency in negotiating the practical and discursive dimensions of breastfeeding in relation to the state and the church. Second, it is related to Karo culture in which mothers have a special treatment in Karo community, mostly because they are breastfeeding. Third, it is related to the continued influence of Karo culture in which the breastfeeding practice is influenced by the central figure of Karo community, i.e. the grandmother. This research provided a new knowledge about ethnic women’s experiences in the breastfeeding practice. Further, the research needs to be enriched with the experiences of voiceless women in breastfeeding practices.Studi ini bertujuan untuk memahami praktik menyusui para ibu di Tanah Karo, Sumatera Utara, Indonesia. Penelitian mengunakan pendekatan etnografi dengan melakukan teknik pengumpulan data seperti observasi partisipan, wawancara formal dan percakapan informal atau perbincangan sehari-hari. Penelitian melibatkan 27 informan. Penelitian menunjukkan bahwa para ibu dipengaruhi oleh negara, agama, dan tradisi etnis. Studi mengidentifikasi tiga temuan esensial terkait dengan praktik menyusui para ibu di Tanah Karo. Pertama, para ibu menunjukkan sisi agensi atau kemandirian terkait praktik menyusui khususnya di hadapan kebijakan negara dan agama. Kedua, terkait dengan kultur Karo, para ibu memperoleh perlakuan yang istimewa, khususnya karena sedang menyusui. Ketiga, masih terkait dengan kultur Karo, praktik menyusui para ibu dipengaruhi oleh figur sentral yakni nenek. Studi ini memperkaya kajian terkait pengalaman perempuan dengan latar belakang etnisitas. Penelitian lebih lanjut perlu dilanjutkan dan diperkaya khususnya terkait dengan pengalaman perempuan marginal atau minoritas dalam hal praktik menyusui.